The role of endothelial dysfunction and subclinical inflammation in the development of obstetric and perinatal complications in diabetes mellitus patients - Yu. A. Dudareva; D. N. Seroshtanova (Acta Biomedica Scientifica, 2021)
Diabetes mellitus in pregnant women is one of the topical problems of modern medicine. Recently, there has been an increase in cases of type 2 diabetes, especially an increase in the frequency of early onset in children and adolescents, respectively, in the fertile age, in a few years; they will enter with the burden of pathology. This is particularly problematic and important during pregnancy, since type 1 and type 2 diabetes are accompanied by a high risk of adverse obstetric and perinatal complications, which are detected in most women with type 1 and type 2 diabetes. The purpose of this review was to assess the role of vascular endothelial dysfunction and subclinical inflammation in the genesis of placental insufficiency causing the development of a number of pregnancy complications in diabetes mellitus, to search for biological markers of these processes, which may reveal some pathogenetic mechanisms for the formation and diagnosis of these disorders.The review shows changes in the content of a number of biological markers, primarily such as pro-inflammatory cytokines (IL-1, TNFα, IL-6); CRP, for certain pregnancy complications in diabetes mellitus women. It is the imbalance of cytokines that very often determines the development of gestational complications and disrupts immunological tolerance in the mother-placenta-fetus system. The degree of severity of angiogenesis processes depends on the level of hyperglycemia, manifestations of subclinical inflammation and is reflected in the increase in the VEGF expression level and its receptors in terminal and stem villi of the placenta.Thus, the review shows the role of endothelial dysfunction and subclinical inflammation in the development of obstetric and perinatal complications in diabetes mellitus patients, which is indicated by the changes in a range of proinflammatory cytokines and other biologically active markers.